Single Strand Conformation Polymorphism Method for Initial Detection DNA Sequences Homogeneity - Topik Hidayat; Adi Pancoro (Bogor Agricultural University, Indonesia, 2010)
In molecular phylogenetic study, homogeneity of DNA sequences is a prerequisite before putting it into practice. Internal transcribed spacer (ITS) region of nuclear ribosomal DNA (nrDNA) has been common in phylogenetic study, but a homogenous sequence is often difficult to obtain. Here we use single-stranded conformation polymorphism (SSCP) method to detect homogeneity for nine pooled amplified products of ITS region. Our results suggested that SSCP method has been applicable in detection homogeneity of ITS region prior to using it in sequencing processes.